This means this, this means that a user's guide to semiotics - Hall, Sean (London Laurence King Publishing, 2012)
Semiotics is the theory of signs, and reading signs is a part of everyday life: from road signs that point to a destination, to smoke that warns of fire, to the symbols buried within art and literature. Semiotic theory can, however, appear mysterious and impenetrable. This introductory book decodes that mystery using visual examples instead of abstract theory. This new edition features an expanded introduction that carefully and clearly presents the world of semiotics before leading into the book's 76 sections of key semiotic concepts. Each short section begins with a single image or sign, accompanied by a question inviting us to interpret what we are seeing. Turning the page, we can compare our response with the theory behind the sign, and in this way, actively engage in creative thinking. A fascinating read, this book provides practical examples of how meaning is made in contemporary culture.
Introduction -- Acknowledgments -- 1. Signs and Signing -- Signifier and Signified -- Sign -- Icon -- Index -- Symbol -- Sender -- Intention -- Message -- Transmission -- Noise -- Receiver -- Destination -- Feedback -- 2.Ways of Meaning -- Simile -- Metaphor -- Metonym -- Synecdoche -- Irony -- Lies -- Impossibility -- Depiction -- Representation -- 3.Conceptual Structures -- Truth and Falsity -- Sameness and Difference -- Wholes and Parts -- Subjectivity and Objectivity -- Appearance and Reality -- Continuity and Discontinuity -- Sense and Reference -- Meaningful and Meaningless -- Problem and Solution -- 4.Visual Structures -- Viewer and Image -- Ideal and Real -- Given and New -- Center and Margin -- Foreground and Background -- Proximity and Presence -- Before and After -- Past, Present, and Future -- Fast and Slow -- 5.Textual Structures -- Readers and Texts -- Words and Images -- Functions -- Forms -- Placing -- Prominence -- Voices -- Intertextuality and Intratextuality -- Paratext and Para language -- 6.Matters of Interpretation -- Concepts and Conceptions -- Connotation and Denotation -- Langue and Parole -- Combinations and Substitutions -- Tokens and Types -- Rule-following -- Conventions -- Classifications -- Understanding and Misunderstanding -- 7. Framing Meaning -- Semantic Units -- Genres -- Styles -- Stereotypes -- Institutions -- Ideologies -- Discourses -- Myths -- Paradigms -- 8. Stories and Storytelling -- Fact and Fiction -- Narratives -- Legends -- Characters and Personas -- Viewpoints -- Mysteries -- Tensions -- Turning points -- Resolutions -- Conclusion -- Bibliography -- Picture Credits.
Keywords: Semiotics; Signs and symbols